2020
DOI: 10.20944/preprints202005.0070.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Role of Temperature in COVID-19 Disease Severity and Transmission Rates

Abstract: Air temperature and body temperature may influence COVID-19 disease severity and transmission rates. In vitro data indicate that SARS-CoV-2 loses infectivity at normal core body temperature (37°C); however, small reductions in temperature proximate to 37°C may result in substantially increased viral stability. If these results are representative of viral decay rates in vivo, then cooler temperatures in the body may enable more rapid viral growth. Breathing cool air—even as warm as 25&… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…The in vitro stability of SARS-CoV-2 experiments has shown that the virus is highly stable at 4 C but is sensitive to heat (Chin et al, 2020) and SARS-CoV-2 loses infectivity at normal core body temperature (37 C). However, small reductions at temperatures close to 37 C may substantially increase its viral stability (Kang, 2020). Many recent studies cited here have suggested a correlation between weather conditions and the COVID-19 pandemic in a similar way to other viral infections such as influenza.…”
Section: Introductionmentioning
confidence: 56%
“…The in vitro stability of SARS-CoV-2 experiments has shown that the virus is highly stable at 4 C but is sensitive to heat (Chin et al, 2020) and SARS-CoV-2 loses infectivity at normal core body temperature (37 C). However, small reductions at temperatures close to 37 C may substantially increase its viral stability (Kang, 2020). Many recent studies cited here have suggested a correlation between weather conditions and the COVID-19 pandemic in a similar way to other viral infections such as influenza.…”
Section: Introductionmentioning
confidence: 56%
“…In addition to the evidence that low temperatures increased the stability and viability of the virus, inhalation of cold air at the initial virus exposure time, can make the upper airway more suitable for viral replication [34, 4], resulting in large viral load, and potentially more severe adverse outcomes. On the other hand, how the temperature that patients were exposed to after symptom onset affect immune responses is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the rising temperature could partially inactivate the viral infection by a long-lasting fever. Fever could alter the complex homeostatic regulation of the human body [219] [220].…”
Section: The Hypothesismentioning
confidence: 99%